“EVALUACIÓN DEL EFECTO INHIBITORIO DE LOS ACEITES ESENCIALES DE NARANJA (Citrus sinensis) EN DOS ESTADOS DE MADUREZ SOBRE EL HONGO Lasiodiplodia theobromae IN VITRO” - López Ortega, María De Los Ángeles (2025)
Essential oils extracted from the peel of green and ripe Valencia oranges (Citrus sinensis) were evaluated as antifungal agents against the phytopathogenic fungus Lasiodiplodia theobromae, which causes significant post-harvest losses